Justice and Internal Displacement. (May 2023) - Draper, Jamie
This article develops a normative theory of the status of 'internally displaced persons'. Political theorists working on forced migration have paid little attention to internally displaced persons, but internally displaced persons bear a distinctive normative status that implies a set of rights that its bearer can claim and correlate duties that others owe. This article develops a practice-based account of justice in internal displacement, which aims to answer the questions of who counts as an internally displaced person and what is owed to internally displaced persons (and by whom). The first section addresses the question of who counts as an internally displaced person by offering an interpretation of the conditions of non-alienage and involuntariness . The second section articulates an account of what is owed to internally displaced persons that draws on and refines the idea of 'occupancy rights'. The third section sets out an account of the role of the international community in supplementing the protection of internally displaced persons by their own states.